Development of indirect competitive ELISA using egg yolk-derived immunoglobulin (IgY) for the detection of Gentamicin residues. Issue 1 (2nd January 2016) - He, Jinxin; Hu, Jianjun; Thirumalai, Diraviyam; Schade, Ruediger; Du, Enqi; Zhang, Xiaoying
Abstract: Gentamicin (Gent) is an aminoglycoside antibiotic being used in livestock sector. Gent residues could cause some genetic disorders by nonsense mutations. This study aimed to develop IgY-based ELISA for the detection of Gent in animal products. Gent was conjugated with Bovine serum albumin (BSA) by carbodiimide method for further immunization in the laying chickens. PEG-6000 extraction method was employed to extract IgY from the egg yolk. The titer of anti-Gent-IgY attained the peak of 1:256, 000 after the 5 th booster immunization. Checkerboard titration confirmed that, anti-Gent IgY in 1:2, 000 dilution could give an Optical Density (OD) 1.0 at 2 µg mL −1 of Gent-OVA coating concentration. IgY-based indirect competitive ELISA (Ic-ELISA) showed that, the IC50 value of anti-Gent IgY was 2.69 ng mL −1 and regression curve equation was y = −16.27x + 56.97 ( R 2 = 0.95, n = 3), confirming that, the detection limit (LOD, IC10 value) was 0.01 ng mL −1 . Recoveries from fresh milk, pork and chicken samples were ranged from 69.82% to 94.32%, with relative standard deviation lower than 10.88%. Our results suggested that generated anti-Gent IgY antibodies can be used in routine screening analysis of Gent residues in food samples.